PENGARUH MODAL KERJA DAN KEBIJAKAN PENDANAAN TERHADAP PROFITABILITAS PERUSAHAAN FARMASI - Zulhaq, Arifah; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the influence of cash turnover, account receivables turnover, inventory turnover and debt to equity ratio to the profitability. The sample selection has been done by using purposive sampling at pharmaceutical companies which are listed in Indonesia Stock Exchange (IDX) with the selected criteria i.e.pharmaceutical companies which have financial report data in 2011-2015 periods, the pharmaceutical companies which have been listing in Indonesia since 1990. Based on research methods, it shows that 6 pharmaceutical companies have been obtained as samples. The analysis technique has been done by using multiple linear regressions analysis, F test, t test, and test classic assumptions. The result of the research indicates that account receivable turnover gives positive and significant influence to the profitability, cash turnover gives significant and negative influence to the profitability and debt to equity ratio gives significant and negative influence to the profitability. Meanwhile, inventory turnover does not give any significant and negative influence to the profitability.Keywords: accounts receivable turnover, debt to equity ratio, profitability